Internal Rate of Return: controversies and interpretations - Barbieri, José Carlos; Álvares, Antonio Carlos Teixeira; Machline, Claude (Revista Gestão da Produção Operações e Sistemas, 2007)
This article demonstrates that the Internal Rate of Return (IRR) has several controversial points for which no solution is in sight. As will be shown in most cases, the IRR does not represent a correct measure of return on investment. The IRR only represents the return on invested capital in those cases where there are conventional flows characterized by an initial outlay and final receipt. These flows are typical of certain financial applications, but rare in the scope of production and operations projects. Intermediary cash flows that occur with great frequency in projects in these areas strip IRR of its condition as a means to measure the return on investment. The objective of this study is to offer a more appropriate interpretation of the multiple rates of return phenomena that may be found in unconventional cash flows and validate the modified internal rate of return (MIRR) as a more acceptable indicator to estimate the rate of return for a conventional investment project. In conclusion, the article shows that for certain unconventional cash flows in which there are multiple solutions for the IRR, even the MIRR is in need of financial meaning. Keywords: Economic Engineering; project evaluation; cash flow analysis; internal rate of return; rate of reinvestment; modified internal rate of return.